Cocoon Silk-Derived, Hierarchically Porous Carbon as Anode for Highly Robust Potassium-Ion Hybrid Capacitors - Luo, Haiyan; Chen, Maoxin; Cao, Jinhui; Zhang, Meng; Tan, Shan; Wang, Lei; Zhong, Jiang; Deng, Hongli; Zhu, Jian; Lu, Bingan (Nano-micro letters, 2020)
Highlights The hierarchically porous nitrogen-doped carbon (SHPNC) was fabricated by biorenewable carbon sources. The SHPNC electrode exhibited a high specific capacity, excellent cyclic stability, and superior rate capability. The asymmetric potassium-ion hybrid capacitors delivered a maximum energy density of 135 Wh kg −1 , long lifespan with excellent capacity retention, and outstanding ultrafast charge/slow discharge performance. Potassium-ion hybrid capacitors (KIHCs) have attracted increasing research interest because of the virtues of potassium-ion batteries and supercapacitors. The development of KIHCs is subject to the investigation of applicable K + storage materials which are able to accommodate the relatively large size and high activity of potassium. Here, we report a cocoon silk chemistry strategy to synthesize a hierarchically porous nitrogen-doped carbon (SHPNC). The as-prepared SHPNC with high surface area and rich N-doping not only offers highly efficient channels for the fast transport of electrons and K ions during cycling, but also provides sufficient void space to relieve volume expansion of electrode and improves its stability. Therefore, KIHCs with SHPNC anode and activated carbon cathode afford high energy of 135 Wh kg −1 (calculated based on the total mass of anode and cathode), long lifespan, and ultrafast charge/slow discharge performance. This study defines that the KIHCs show great application prospect in the field of high-performance energy storage devices.